Anorectic and aversive effects of GLP-1 receptor agonism are mediated by brainstem cholecystokinin neurons, and modulated by GIP receptor activation - Alessia Costa; Minrong Ai; Nicolas Nunn; Isabella Culotta; Jenna Hunter; Mehdi Boutagouga Boudjadja; Lourdes Valencia-Torres; Gabriella Aviello; David J. Hodson; Brandy M. Snider; Tamer Coskun; Paul J. Emmerson; et al. (Elsevier, 2022)
Objective: Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are effective medications to reduce appetite and body weight. These actions are centrally mediated; however, the neuronal substrates involved are poorly understood. Methods: We employed a combination of neuroanatomical, genetic, and behavioral approaches in the mouse to investigate the involvement of caudal brainstem cholecystokinin-expressing neurons in the effect of the GLP-1RA exendin-4. We further confirmed key neuroanatomical findings in the non-human primate brain. Results: We found that cholecystokinin-expressing neurons in the caudal brainstem are required for the anorectic and body weight-lowering effects of GLP-1RAs and for the induction of GLP-1RA-induced conditioned taste avoidance. We further show that, while cholecystokinin-expressing neurons are not a direct target for glucose-dependent insulinotropic peptide (GIP), GIP receptor activation results in a reduced recruitment of these GLP-1RA-responsive neurons and a selective reduction of conditioned taste avoidance. Conclusions: In addition to disclosing a neuronal population required for the full appetite- and body weight-lowering effect of GLP-1RAs, our data also provide a novel framework for understanding and ameliorating GLP-1RA-induced nausea - a major factor for withdrawal from treatment.